Minimizing Black Hole Attack In Mobile Ad Hoc Network With Anomaly Based Ids Approach - Worku, Ayalew (ASTU, 2019)
Mobile Ad hoc Network suffers from many attacks due to a lack of centralized authorized system. In the existing works, the protection mechanisms of a network from attacks are by using only encryption-decryption software and firewalls, which have less security. Since MANET has no authorized system, it exposes too many attacks such as jellyfish attack, the man in the middle attack, selfish node attack, wormhole attack, Dos attack, Sybil attack, and black hole attack. Among those attacks, black hole attack is a realistic and difficult attack in MANET. It against network integrity, confidentiality, and availability by absorbing and dropping data packets in the network while the sender node sends to the destination node. Due to the interruption of the black-hole attack, data packets cannot reach to the target node. Black Hole Attack damage mobile nodes by sending a forged RREP immediately to the sender node before the receiver node reply. In this thesis work, we evaluate the impact of single black hole attack as well as multiple black hole attack and minimize its consequence by applied Anomaly based IDS approach under Ad hoc on Demand Multipath Distance Vector to improve the performance of MANET. As we have seen, the simulation result using NS2 the proposed ABIDS approach is an efficient approach to reduce black hole attack in terms of Jitter, Throughput, and End to end delay. This regards the performance of AOMDV protocol is improved in MANET because of using the proposed ABIDS approach.
Keywords: MANET, SBHA, MBHA, ABIDS, AOMDV, and BHA